Diseño y construcción de un dispositivo para la movilización de autos colisionados que permita la reducción del tiempo en un taller - Espinosa Martínez, David Andres (2017)
This project has the purpose of designing a device that allows the easy transportation of collapsed light vehicles that have a maximum weight of 1.8 Ton, inside an automotive workshop. First Chapter will provide a brief explanation of the types of collisions and the most frequent statistics presented by the national transit agency, as well as the systems currently used for the mobilization of vehicles within a workshop and their intervention inside the workflow. Second chapter shows a study of possible alternatives that can be implemented to meet this need for mobility within the workshop. Third Chapter details the design and simulation of the parts that make up the device for easy transfer of collided vehicles (FTVC), which is composed of four essential parts are the steering wheel, the telescopic arms, the chassis and the lock . Fourth Chapter details the economic resources that are used for the construction of the FTVC device and the results obtained in the tests with the same.